Perception of local communities on protected areas: lessons drawn from the Bale Mountains National Park, Ethiopia - Gulte, E.; Tadele, H.; Haileslassie, Amare; Mekuria, Wolde (Informa UK Limited, 2023)
A study targeting the Bale Mountains National Park in Ethiopia was conducted to gain a deeper understanding of local communities’ opinion on benefits and disbenefits of protected areas and existing benefit-sharing mechanisms and to suggest future research for development direction related to the management of protected areas. Household surveys, key informant interviews and focus group discussions were tools used to collect data. The results obtained through the analysis of the factors affecting the attitude of local communities on the park and its management demonstrated that efforts should be concentrated on improving communication with local communities and short-term economic benefits as well as identifying the reasons for the unhealthy relationships and addressing them. These issues can partly be addressed through creating and supporting effective and functioning multistakeholder platforms for dialogue and co-production of knowledge, continuous meetings and awareness-raising campaigns and integrating more income-generating activities. The results also suggested that park management and government authorities use their authority to decide how local communities should participate in Bale Mountains National Park management initiatives. Such a top-down approach affects the sustainability of the efforts to conserve protected areas because local stakeholders lack incentives to participate. This also leads to inadequate understanding of the complex relationships between people and protected areas they depend on and the inability to tailor management responses to specific needs and conditions. The study discussed the implications of the results for future planning and management of protected areas and forwarded recommendations for policy and future research for development directions.